PERFORMANCE EVALUATION OF FOXTAIL MILLET VARIETIES IN RAINFED ALFISOLS - C. RADHA KUMARI* and B. SAHADEVA REDDY, (The Journal of Research ANGRAU, 2023)
The field experiment was conducted to study the suitability of foxtail millet varieties for Alfisols of scarce rainfall zone under rainfed conditions for two years during Kharif 2014-15 and 2015-16 at Agricultural Research Station, Ananthapuramu. The treatments consisted of six varieties viz., Narasimharaya, Krishnadevaraya, Srilakshmi, SiA 3085, Prasad and Suryanandi. The results revealed that SiA 3085, Narasimharaya and Srilakshmi produced significantly higher grain yield when compared to the remaining tested varieties. Narasimharaya and Krishnadevaraya can be recommended for dual purpose (both for grain and straw) followed by Srilakshmi variety. SIA - 3085 variety has to be recommended for grain production on commercial basis as its potential for production of straw is low.